Implementation and control of a tri-state DC-DC step-up converter - Goh, Cheng Loo. (2009)
This report describes the design, implementation and control of a tri-state dc-dc step-up converter with fast dynamics. The step-up converter converts a lower input dc voltage to a higher dc output voltage. The feedback controllers implemented are adaptive controllers with different structures. Experimental results of the tri-state step-up converter are provided to illustrate the dynamic performances of these controllers under different operating conditions. The controllers are also compared with respect to their design and closed-loop performances.